Altered Fecal Microbiota in Paediatric Inflammatory Bowel Disease. (8th September 2015) - Maukonen, Johanna; Kolho, Kaija-Leena; Paasela, Monika; Honkanen, Jarno; Klemetti, Paula; Vaarala, Outi; Saarela, Maria
Abstract : Background and Aims: Several factors support the view of inflammatory bowel disease [IBD] origin in the host responsiveness to intestinal bacteria, although no single bacterial species has been shown as a causative agent in the pathogenesis. Our aim was to analyse the fecal microbiota of paediatric IBD patients at different stages of the disease. In addition, the characteristics of immune response to the bacterial isolates showing very low abundance in IBD were studied. Methods: Fecal samples [1–3 samples/child] were collected from 10 paediatric patients with crohn's disease [CD], ] and 12 with ulcerative colitis [UC] and from 8 healthy children, for polyphasic microbiological analysis (culture, real-time polymerase chain reaction [PCR], and denaturing gradient gel electrophoresis). In addition, in vitro cytokine responses of peripheral blood mononuclear cells to the bacterial isolates, which showed very low abundance in IBD, were studied. Results: Although predominant bacterial diversity was higher in IBD, the numbers of Lachnospiraceae and Coriobacteriaceae bacteria were lower in IBD patients as compared with control children [ p < 0.05]. In addition, Ruminococcaceae population diversity was lower in IBD [ p < 0.05] and correlated negatively with fecal calprotectin levels. Both abundance and diversity of bifidobacterial populations were lower in children with IBD [ p < 0.05], and particularly low numbers of certain bifidobacterial isolates were detected. In CD, we found enhanced up-regulation of interleukin-6 transcripts and impaired RAR-related orphan receptor C response to bifidobacteria, whereas decreased interferon-gamma response was observed in both CD and UC. Conclusion: We demonstrate altered fecal microbiota in paediatric IBD, particularly low numbers and diversity of bifidobacterial populations. Interestingly, immunological response to bifidobacteria differed between paediatric CD patients and control children.